Z2nm-supermagic labeling of Cn#Cm - Dalibor Froncek; James McKeown; John McKeown; Michael McKeown (Indonesian Combinatorial Society (InaCombS), 2018)
A Γ-supermagic labeling of a graph G = (V, E) with ∣E∣ = k is a bijection from E to an Abelian group Γ of order k such that the sum of labels of all incident edges of every vertex x ∈ V is equal to the same element μ ∈ Γ. We present a Z2nm-supermagic labeling of Cartesian product of two cycles, Cn□Cm for n odd. This along with an earlier result by Ivančo proves that a Z2nm-supermagic labeling of Cn□Cm exists for every n, m ≥ 3.